Portability improvement for free-space reflectivity measurement. (June 2020) - Zhang, Yunpeng; Li, En; Gao, Chong; Zheng, Hu
Graphical abstract: Highlights: Portable reflectivity test system is proposed based on the near-field test antenna. Vivaldi antenna with the characteristic of near-field plane-like wave is designed. Antenna installation configuration and time-domain gating interval are analyzed. The proposed system has high test precision and wide dynamic range. Proposed system is suitable for the industrial application due to its portability. Abstract: The free-space method is a standard technique for the reflectivity measurement of the absorbing material, where the horn antenna is usually used as the transmitting antenna and receiving antenna. In order to improve the ability to perform reflectivity in-situ measurement using a small sample volume and readily available instrumentation, it is necessary to study the portability of the free-space reflectivity test system. This paper describes a versatile low-cost solution for the reflectivity measurement. By designing a radiation-enhanced Vivaldi antenna and choosing the transceiver configuration reasonably, a portable and broadband reflectivity test system is proposed. As a demonstration, reflectivity measurement of the absorbing sheets is experimentally demonstrated in the band of 2–18 GHz, good consistency with the test result from the standard arch system shows that the proposed system is a very adapted candidate for the industrial application.